Active methodologies and academic performance in agricultural engineering students at the National University of Loja - Jiménez Román, Mishell Kruskaya (2025)
Higher education faces significant challenges, one of which is the shift from traditional teaching methodologies to student-centered, active methodologies. These foster active student participations and, above all, the development of critical thinking, making them key tools in educational processes. Furthermore, problems have been observed in the academic performance of Engineering students at the National University of Loja. Therefore, the objective of this research is to analyze the relationship between active methodologies and the academic performance of Agricultural Engineering students. A quantitative approach was used, with a non-experimental, descriptive-correlational, and cross-sectional design. Data collection was conducted using an ad hoc questionnaire administered to students in the final years of the program. In addition, grades for the second unit were collected from participating students. It was determined that the most commonly used methodologies were project-based learning (PBL), flipped classrooms, and cooperative work. Students positively value the methodological renewal but identify limited use of space and resources. Furthermore, there is a moderate positive relationship between methodological renewal and academic performance, and a weak positive relationship between the use of lectures and academic performance. It is concluded that active methodologies and students' grade point averages have a low positive correlation. Therefore, the greater the use of active methodologies by teachers, the better the academic performance of Agricultural Engineering students.